Utilization Of Kepok Banana Peel (Musa Paradisiaca) As An Adsorbent To Reduce Levels Of Plus Metal In Paint And Body Repair Industrial Waste - Jesica Amelia Kischa Parante; Sinardi Sinardi (International Journal of Health Engineering and Technology, 2026)
The increasing activity of paint and body repair workshops has contributed to the increasing volume of liquid waste containing heavy metals, especially lead (Pb), which is toxic and has the potential to pollute aquatic environments. Long-term exposure to Pb can have negative impacts on human health and ecosystem balance, so that effective, economical, and environmentally friendly waste treatment efforts are needed. One alternative that can be applied is the use of natural materials as adsorbents, such as kepok banana peels (Musa paradisiaca), which contain cellulose, hemicellulose, and lignin with active functional groups that have the potential to bind heavy metal ions. This study aims to determine the effect of variations in contact time on the adsorption efficiency of Pb metal and evaluate the ability of kepok banana peels as a natural adsorbent in reducing Pb levels in paint and body repair workshop wastewater. The research method used is an adsorption process with contact time variations of 0, 30, 60, 90, 120, and 150 minutes. The parameters observed include the initial concentration of Pb (C₀), the final concentration of Pb (Ct), the amount of Pb absorbed, and the removal efficiency. The results showed that increasing the contact time significantly affected the effectiveness of the adsorption process. The Pb removal efficiency increased gradually from 0.00% at 0 minutes to 47.69% at 90 minutes of contact time, which is the optimum condition for adsorption. At that time, the Pb concentration decreased from 0.65 mg/L to 0.34 mg/L, with the amount of Pb adsorbed reaching 0.31 mg/L. However, after passing the optimum contact time, the adsorption efficiency decreased at 120 and 150 minutes, which was thought to be caused by adsorbent saturation and the possibility of a desorption process. Based on the results obtained, it can be concluded that kepok banana peel has quite good potential as a natural adsorbent in reducing Pb metal levels from paint and body repair workshop industrial waste. The utilization of this organic waste is not only effective in the waste treatment process, but also supports the concept of sustainable environmental management through the application of simple, inexpensive, and environmentally friendly technology.